Trust in government regarding COVID-19 and its associations with preventive health behaviour and prosocial behaviour during the pandemic:a cross-sectional and longitudinal study - Han, Qing; Zheng, Bang; Cristea, Mioara; Agostini, Maximilian; Belanger, Jocelyn J; Gutzkow, Ben; Kreienkamp, Jannis; Collaboration, PsyCorona; Abdul Khaiyom, Jamilah Hanum; Leander, N Pontus (Cambridge University Press, 2021)
Background. The effective implementation of government policies and measures for controlling the coronavirus disease 2019 (COVID-19) pandemic requires compliance from the public. This study aimed to examine cross-sectional and longitudinal associations of trust in government regarding COVID-19 control with the adoption of recommended health behaviours and prosocial behaviours, and potential determinants of trust in government during the pandemic.